Influence of ligand binding on structure and thermostability of human α1-acid glycoprotein - Kopecký, Vladimír; Ettrich, Rüdiger; Pazderka, Tomáš; Hofbauerová, Kateřina; Řeha, David; Baumruk, Vladimír (Journal of molecular recognition, 2016)
Ligand binding of neutral progesterone, basic propranolol, and acidic warfarin to human α1-acid glycoprotein (AGP) was investigated by Raman spectroscopy. The binding itself is characterized by a uniform conformational shift in which a tryptophan residue is involved. Slight differences corresponding to different contacts of the individual ligands inside the β-barrel are described. Results are compared with in silico ligand docking into the available crystal structure of deglycosylated AGP using quantum/molecular mechanics. Calculated binding energies are -18.2, -14.5, and -11.5 kcal/mol for warfarin, propranolol, and progesterone, respectively. These calculations are consistent with Raman difference spectroscopy; nevertheless, minor discrepancies in the precise positions of the ligands point to structural differences between deglycosylated and native AGP. Thermal dynamics of AGP with/without bounded warfarin was followed by Raman spectroscopy in a temperature range of 10-95 °C and analyzed by principal component analysis. With increasing temperature, a slight decrease of α-helical content is observed that coincides with an increase in β-sheet content. Above 45 °C, also β-strands tend to unfold, and the observed decrease in β-sheet coincides with an increase of β-turns accompanied by a conformational shift of the nearby disulfide bridge from high-energy trans-gauche-trans to more relaxed gauche-gauche-trans. This major rearrangement in the vicinity of the bridge is not only characterized by unfolding of the β-sheet but also by subsequent ligand release. Hereby, ligand binding alters the protein dynamics, and the more rigid protein-ligand complex shows an improved thermal stability, a finding that contributes to the reported chaperone-like function of AGP.
Keywords: stabilita proteinů; sekundární struktura proteinů; termodynamika; Tryptophan; Models, Molecular; tryptofan; Spectrum Analysis, Raman; simulace molekulového dockingu; Protein Binding; Warfarin; binding site; warfarin; propranolol; Molecular Docking Simulation; orosomucoid; thermal stability; Protein Stability; Thermodynamics; Orosomucoid; progesteron; molekulární modely; Protein Structure, Secondary; molecular modeling; Humans; Binding Sites; vazba proteinů; Progesterone; Raman spectroscopy; Propranolol; orosomukoid; vazebná místa; Ramanova spektroskopie; lidé